Between the lines - Fourie, Michael (My University, 2010)
The purpose of this dissertation is twofold: i) to explore and propose a design to enlarge, improve and revitalize Beyers Naude Square and ii) upgrade and extend the Johannesburg Public Library in the Johannesburg CBD to fulfill its potential as a modern, effective public information facility. This project will be planned and designed with two main aims: Firstly to improve the library and the service it provides by meeting its needs for space and modernization and secondly to design the public square and new library extension in such a way that their combined implementation will embrace the city’s past and present, and express the Nation's confidence in its future.